2022
DOI: 10.1186/s12936-022-04058-0
|View full text |Cite
|
Sign up to set email alerts
|

Trends in malaria epidemiological factors following the implementation of current control strategies in Dangassa, Mali

Abstract: Background Over the past decade, three strategies have reduced severe malaria cases and deaths in endemic regions of Africa, Asia and the Americas, specifically: (1) artemisinin-based combination therapy (ACT); (2) insecticide-treated bed nets (ITNs); and, (3) intermittent preventive treatment with sulfadoxine-pyrimethamine in pregnancy (IPTp). The rationale for this study was to examine communities in Dangassa, Mali where, in 2015, two additional control strategies were implemented: ITN univer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Furthermore, a four quarterly survey of 7,000 children less than 10 years old in Ethiopia found that the incidence rate varied between 2.4 and 20% in high-altitude areas, depending on the quarter of the year [ 12 ]. A study conducted in Mali among 1401 participants (over 65% less than 20 years) from 2012 to 2020, reported significantly different estimates at the start and end of the rainy season, demonstrating the impact of seasonality/transmission intensity on malaria distribution [ 13 ]. The disparity in published estimates can be attributed to differences in patient inclusion, malaria case definition, assumptions made in the estimation, differences in seasonality, and transmission intensity [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a four quarterly survey of 7,000 children less than 10 years old in Ethiopia found that the incidence rate varied between 2.4 and 20% in high-altitude areas, depending on the quarter of the year [ 12 ]. A study conducted in Mali among 1401 participants (over 65% less than 20 years) from 2012 to 2020, reported significantly different estimates at the start and end of the rainy season, demonstrating the impact of seasonality/transmission intensity on malaria distribution [ 13 ]. The disparity in published estimates can be attributed to differences in patient inclusion, malaria case definition, assumptions made in the estimation, differences in seasonality, and transmission intensity [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Dangassa, the prevalence of asymptomatic infection decreased from 60.3% in 2012 to just 18.5% in 2020. 25 In Dioro, prevalence rates abruptly increased from 32.8% in 2012 to 61.6% in 2014 (following the discontinuation of universal healthcare access supported by the MVP). In Koulikoro, the newest WA-ICEMR site established in 2018, the prevalence of asymptomatic infection declined from 11.5% in 2018 to 7.3% in 2020.…”
Section: Insights From Research Activities Have Enriched the Understa...mentioning
confidence: 99%
“… 14 16 However, there is also a possibility that old age and the presence of non-communicable diseases (NCDs) lead to the attenuation of this immunity. 17 , 18 These may put elderly persons at a significantly higher risk of malaria and its unacceptable sequelae. 15 , 19 , 20 …”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] However, there is also a possibility that old age and the presence of non-communicable diseases (NCDs) lead to the attenuation of this immunity. 17,18 These may put elderly persons at a significantly higher risk of malaria and its unacceptable sequelae. 15,19,20 Moreover, the burden of NCDs is increasing among older adults in many economically developing countries, including Nigeria.…”
Section: Introductionmentioning
confidence: 99%